The Effect of Tea (Camelia sinensis) and Chocolate (Theobroma cacao) on Memory - Justin Himawan; Santoso Santoso; Mochamad Ali Sobirin; Endang Mahati (Journal of Applied Food Technology, 2021)
Memory is often understood as an informational processing system with explicit and implicit functioning that is made up of a sensory processor, short-term (working) memory, long-term memory. Tea (Camellia sinensis) and chocolate (Theobroma cocoa) are common food beverages containing caffeine, theobromine, and flavonoid. Those substances in recent studies showed positive impact on cognitive performance. We examined the relation between the intake of both drinks on memory. The objectives are to determine the effect of black tea and chocolate on visuospatial memory. Eighteen males, 20 – 35 g body weight mice used as the subject that given by tea and chocolate for 28 days and experimented with Morris Water Maze Test. The study showed that there is significant effect on mice that given both tea (p=0.006) and chocolate (p=0.006) on memory as compared to control mice. However, there is no significant difference between the effect of tea and chocolate on memory. There is positive impact of consumption on both tea and chocolate on memory, especially visuospatial memory. Tea and chocolate significantly decrease the time of the mice to locate the platform.